"We can't wait for the bugs to spread" rhetorics of time, space and biosecurity in global health law. (3rd April 2018) - Harrington, John
ABSTRACT: Work on global health law is often based on a diffusionist and functionalist model which sees legal initiatives from 'centres', such as Washington or Geneva, responding to new disease threats and a lack of capacity at the 'periphery', say in Sierra Leone or southern China. This approach overlooks the significance of national institutions and contexts, and neglects the rhetorical dimension of global governance, obscuring the influence of colonial idioms and practices. This paper proposes an alternative model, based on nodal governance theory, capable of accounting for these neglected dimensions. It argues that global health interventions are structured discursively by a range of spatio-temporal figures ('chronotopes') which have persuasive force owing to their wider historic resonances. This is explored through the example of a 2010 United States effort to secure pathogens stored in East African research laboratories against terrorist groups. A high-level team argued that Congress should fund training and infrastructure. The case was shaped rhetorically by various chronotopes including that of Africa as a natural source of disease, the 'regression' of states in the region to failed status, and the ineffectiveness of national borders after globalisation.